Intra-Specific Venom Variation in the Australian Coastal Taipan Oxyuranus scutellatus - Theo Tasoulis; Anjana Silva; Punnam Chander Veerati; Mark Baker; Wayne C. Hodgson; Nathan Dunstan; Geoffrey K. Isbister (Toxins, 2020)
Intra-specific venom variation has the potential to provide important insights into the evolution of snake venom, but remains a relatively neglected aspect of snake venom studies. We investigated the venom from 13 individual coastal taipans Oxyuranus scutellatus from four localities on the north-east coast of Australia, spanning a distance of 2000 km. The intra-specific variation in taipan venom was considerably less than the inter-specific variation between it and the other Australian elapids to which it was compared. The electrophoretic venom profile of O. scutellatus was visually different to six other genera of Australian elapids, but not to its congener inland taipan O. microlepidotus. There was minimal geographical variation in taipan venom, as the intra-population variation exceeded the inter-population variation for enzymatic activity, procoagulant activity, and the abundance of neurotoxins. The pre-synaptic neurotoxin (taipoxin) was more abundant than the post-synaptic neurotoxins (3FTx), with a median of 11.0% (interquartile range (IQR): 9.7% to 18.3%; range: 6.7% to 23.6%) vs. a median of 3.4% (IQR: 0.4% to 6.7%; range: 0% to 8.1%). Three taipan individuals almost completely lacked post-synaptic neurotoxins, which was not associated with geography and occurred within two populations. We found no evidence of sexual dimorphism in taipan venom. Our study provides a basis for evaluating the significance of intra-specific venom variation within a phylogenetic context by comparing it to the inter-specific and inter-generic variation. The considerable intra-population variation we observed supports the use of several unpooled individuals from each population when making inter-specific comparisons.